2020
DOI: 10.1017/s1355617720000909
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Memory Impairment in Parkinson’s Disease: Disentangling the Role of Encoding and Retrieval

Abstract: Objective: The source of episodic memory (EM) impairment in Parkinson’s disease (PD) is still unclear. In the present study, we sought to quantify specifically encoding, consolidation, and retrieval process deficits in a list-learning paradigm by a novel method, the item-specific deficit approach (ISDA). Methods: We applied the ISDA method to the Free and Cued Selective Reminding Test (FCSRT) in a sample of 15 PD patients and 15 healthy participants. Results: The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…Nevertheless, PD patients displayed significant poorer performance on executive-inhibition (Hayling B and Trails 3 & 4 from TeSen test). They also reported more impulsivity difficulties (QUIP-RS), executive (BRIEF-A) and memory (MFE) daily problems (also see Siquier & Andrés, 2021a for further details on these patients' episodic memory). With respect to the affective dimensions, participants did not differ in anxiety symptoms (GAD-7).…”
Section: Demographic and Neuropsychological Resultsmentioning
confidence: 94%
“…Nevertheless, PD patients displayed significant poorer performance on executive-inhibition (Hayling B and Trails 3 & 4 from TeSen test). They also reported more impulsivity difficulties (QUIP-RS), executive (BRIEF-A) and memory (MFE) daily problems (also see Siquier & Andrés, 2021a for further details on these patients' episodic memory). With respect to the affective dimensions, participants did not differ in anxiety symptoms (GAD-7).…”
Section: Demographic and Neuropsychological Resultsmentioning
confidence: 94%
“…Growing evidence, however, suggests that at least part of the memory deficit observed in PD also results from poor encoding as a consequence of hippocampal alterations (Brønnick et al, 2011;Chiaravalloti et al, 2014). As it is the case with the Free and Cued Selective reminding test (see Siquier and Andrés, 2021a), an advantage of the FNAME task is that it enables to equate groups for encoding strategies, allowing therefore to rule out the contribution of learning differences to retrieval deficits. Once the groups were equated with respect to encoding, the The mean difference in recall 1, recall 2, and delayed name recall between groups is shown in the Gardner-Altman estimation plots.…”
Section: Discussionmentioning
confidence: 99%
“…However, recognition and cued-recall deficits have also been observed ( Carlesimo et al, 2012 ; Foo et al, 2016 ; Das et al, 2019 ; La et al, 2019 ). For instance, differences in recall performance between individuals with PD and healthy controls may disappear when encoding is equated across groups ( Chiaravalloti et al, 2014 ; Siquier and Andrés, 2021a ). Hence, evidence suggests that memory dysfunction in individuals with PD may reflect hippocampal alterations rather than solely fronto-striatal alterations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of significant difference between PD patients’ performance and elderly controls in the recognition task could be explained by the pattern of memory difficulties of PD patients. Siquier and Andrés (2021) suggested that these difficulties concern particularly memory retrieval processes. Indeed, the participants might not necessarily remember the learned actions in detail (recollection), but might simply have the impression of having already encountered certain action drawings (familiarity) during the encoding phase.…”
Section: Discussionmentioning
confidence: 99%